A Brief Overview on Pesticide Exposure and Ocular Toxicity - Joseph Laquatra (Research Developments in Medicine and Medical Science Vol. 1, 2023)
Pesticide residues accumulate in homes with greater amounts which are found in the Child Breathing Zone. It is well-known that exposure to pesticide residues can have harmful consequences on one’s health, including toxicity to the eyes. This paper describes a study of pesticide residues found in a random sample of 132 homes in non-metropolitan counties of New York State. Fifteen pesticides were tested for and residues from all fifteen pesticides were found in all 132 homes. The effects of human exposure to these residues are discussed. Negative consequences from exposure include conjunctivitis and ocular hyperemia. Other health effects include retinal degeneration, optic neuropathy, retinopathy, ocular motor palsy, and cataracts. McCaule et al. [1] reported that residential cleaning practices can significantly reduce pesticide residues, but those practices are specific to different surfaces.